PENGGUNAAN BERBAGAI DOSIS KOMPOS PADA TANAMAN SUKUN (Artocarpus communis) di DAERAH TANGKAPAN AIR DANAU TOBA KECAMATAN HARANGGAOL HORISON KABUPATEN SIMALUNGUN - Rachel C.M Siregar; Afifuddin Dalimunthe; Budi Utomo (Peronema Forestry Science Journal, 2015)
The condition of critical land in Lake Toba Catchment Area is  the cause of the soil unfertility and  impact on crops. Breadfruit plant that can grow in all types of soil and improving productivity and useful in the greening. Compost is one of the organic fertilizer which can improve soil structure that can support plant growth.   This study aimed to determine the dosage of compost on seedling growth breadfruit plant (Artocarpus communis), and improve the ability of growth of  crops in the field. This research was conducted in the Village District of Haranggaol Horison, Simalungun North Sumatra, from September 2014 to November 2014 by using a non factorial randomized block design with treatment are 0 g, 100 g, 200 g, 300 g, 400 g , 500 g, 600 g, 700 g, 800 g, 900 g, 1000 g with four replications. The results showed that the addition and using compost did not significantly affect to the height, diameter, number of leaves, leaf area, and the vast canopy water content on plant. However, the viability of the plant reached 97.73% indicated breadfruit plant can grow. Giving compost at a dose of 700 g has given the best growth of the plants of breadfruit plant (Artocarpus communis). And C / N ratio showed good results in the amount of 12.47; 13.83; 13.68 as equal to the C / N ratio that allowed the plants to absorb soil nutrients.Keywords: Artocarpus communis, compost, critical land, catchment area